2017
DOI: 10.3390/nu9060580
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hesperidin on the Systemic and Intestinal Rat Immune Response

Abstract: Polyphenols, widely found in edible plants, influence the immune system. Nevertheless, the immunomodulatory properties of hesperidin, the predominant flavanone in oranges, have not been deeply studied. To establish the effect of hesperidin on in vivo immune response, two different conditions of immune system stimulations in Lewis rats were applied. In the first experimental design, rats were intraperitoneally immunized with ovalbumin (OVA) plus Bordetella pertussis toxin and alum as the adjuvants, and orally g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 39 publications
2
28
1
Order By: Relevance
“…In addition, it occurs in a large number of fruits and vegetables such as tomatoes and cherries, and various herbal formulations [148]. Hesperetin and its metabolites display several biological activities including antioxidant, anti-inflammatory, and lipid decreasing levels, anticarcinogenic, antidiabetic, immunoregulatory, and neuroprotective [149,150]. Actually, several in vitro and in vivo studies have been reported that Hesperetin, its metabolites, and its synthetic derivatives augmented the antioxidant cellular defenses such as the ERK/Nrf2 signaling pathway and peroxisome proliferatoractivated receptor-γ (PPAR-γ), reduced inflammatory targets including NF-κB, iNOS, and COX-2, and other markers of chronic inflammation such as IL-1β, IL-6, NO and TNF-α [151][152][153].…”
Section: Hesperetinmentioning
confidence: 99%
“…In addition, it occurs in a large number of fruits and vegetables such as tomatoes and cherries, and various herbal formulations [148]. Hesperetin and its metabolites display several biological activities including antioxidant, anti-inflammatory, and lipid decreasing levels, anticarcinogenic, antidiabetic, immunoregulatory, and neuroprotective [149,150]. Actually, several in vitro and in vivo studies have been reported that Hesperetin, its metabolites, and its synthetic derivatives augmented the antioxidant cellular defenses such as the ERK/Nrf2 signaling pathway and peroxisome proliferatoractivated receptor-γ (PPAR-γ), reduced inflammatory targets including NF-κB, iNOS, and COX-2, and other markers of chronic inflammation such as IL-1β, IL-6, NO and TNF-α [151][152][153].…”
Section: Hesperetinmentioning
confidence: 99%
“…These young rats, also used by other authors 36,70 , were chosen because they would be adults by the end of the training programme. In addition, previous experiments with nutritional interventions were carried out at this age 41 , a period which is sensitive to the immune system enhancement 71 . Animals were housed in the animal facilities of the Faculty of Biology (UB) in polycarbonate cages (2-3 rats per cage) in a controlled environment of temperature and humidity, in a 12/12 h light/dark cycle.…”
Section: Animalsmentioning
confidence: 99%
“…Non-stimulated macrophages were included as control. Supernatants were collected for IFN-γ, IL-1β, IL-6, IL-10, IL-12, MCP-1, and TNF-α quantification by using ProcartaPlex ® Multiplex Immunoassay (Affymetrix, eBioscience, San Diego, CA, USA), as previously described 71 . Data were acquired by Luminex MAGPIX analyzer (Luminex ® ) in the Flow Cytometry Unit of the CCiTUB and analyzed with ProcartaPlex ® Analyst (Thermo Fisher Scientific, S.L.U, Barcelona, Spain).…”
Section: Animalsmentioning
confidence: 99%
“…This Special Issue “Effects of Polyphenol-Rich Foods on Human Health” comprises 64 peer-reviewed papers, including 43 original research papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], one case-report [ 51 ] and 20 literature reviews [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
mentioning
confidence: 99%
“…Polyphenols have been demonstrated to be responsible for the anti-inflammatory and antioxidant properties of potentially functional foods. Numerous studies explored in detail the molecular mechanisms underlying the protective effects of polyphenols, including antioxidant capacity, that can be attributed to the regulation of redox enzymes through reducing reactive oxygen species (ROS) production and modulation of the II-phase enzymes responsible for the cellular oxidative response; other studies explored the chemo-preventive effects of polyphenols, including the elimination of carcinogenic agents, the modulation of pathways responsible for cancer cell signaling and cell cycle progression, and in the promotion of apoptosis [ 8 , 10 , 11 , 12 , 14 , 16 , 18 , 25 , 27 , 29 , 30 , 31 , 32 , 37 , 38 , 40 , 41 , 42 , 47 , 48 , 49 , 50 ].…”
mentioning
confidence: 99%